2009
DOI: 10.1111/j.1440-169x.2009.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of stochastic Ca2+ signals in the formed somites during the early segmentation period in intact, normally developing zebrafish embryos

Abstract: Localized Ca2+ signals were consistently visualized in the formed somites of intact zebrafish embryos during the early segmentation period. Unlike the regular process of somitogenesis, these signals were stochastic in nature with respect to time and location. They did, however, occur predominantly at the medial and lateral boundaries within the formed somites. Embryos were treated with modulators of [Ca 2+ ] i to explore the signal generation mechanism and possible developmental function of the stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
(74 reference statements)
4
12
0
Order By: Relevance
“…The Triton X-100 was used to permeabilize the cardiosphere cells and thus expose any unspent holo-f-aequorin to extracellular Ca 2+ . This confirmed that the low level of aequorin-generated luminescence (and thus the [Ca 2+ ]) observed was real and not due to the Ca 2+ reporter being used up (Leung et al, 2009).…”
Section: Testing the Functionality Of Reconstituted Holo-f-aequorin Isupporting
confidence: 70%
See 1 more Smart Citation
“…The Triton X-100 was used to permeabilize the cardiosphere cells and thus expose any unspent holo-f-aequorin to extracellular Ca 2+ . This confirmed that the low level of aequorin-generated luminescence (and thus the [Ca 2+ ]) observed was real and not due to the Ca 2+ reporter being used up (Leung et al, 2009).…”
Section: Testing the Functionality Of Reconstituted Holo-f-aequorin Isupporting
confidence: 70%
“…This is consistent with the expression of these two SR-based receptors during embryogenesis in animal models, where functional IP 3 Rs have been shown to be expressed in nearly every cell in mice and zebrafish embryos from the earliest stages of development and expression continues throughout development (Rosemblit et al, 1999;Lee et al, 2003;Leung et al, 2009;Cheung et al, 2011). On the other hand, functional RyRs are not expressed during the early stages of development, but they are expressed later on with the differentiation of excitable cells, including cardiac and skeletal muscle, where the receptors are used for specialized cellular functions such as cell contraction (Rosemblit et al, 1999;Lee et al, 2003;Leung et al, 2009;Cheung et al, 2011). Although we demonstrate that IP 3 Rs are functional from day 1 onwards, and that RyRs appear to only be functional at day 8, our current data does not tell us the specific role of either receptor with respect to early differentiation of HES2 ESCs.…”
Section: Determination Of the Presence Of Functional Ip 3 Rs And Ryrssupporting
confidence: 56%
“…Embryos were injected at the one-cell stage with either ~1nL of 25mM NP-EGTA (dissolved in 100mM KCl, 40mM Hepes, pH 7.2) or ~1nL of 25mM diazo-2 (dissolved in 100mM KCl, 10mM EGTA, 10mM MOPS, pH 7.2) as previously described (Leung et al, 2009). At 5dpf, compounds were activated via photolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the sudden appearance of the SP1 transients initially in somites 4 to 10, follow a period of quiescent Ca 2+ signaling as far as the zebrafish trunk is concerned. We have previously reported that a period of relatively localized stochastic Ca 2+ signaling occurs in the formed somites and to a much lesser extent in the pre-somitic mesoderm during the early segmentation period, i.e., during the 1 to 8 somite stages (~10 to 13 hpf; Leung et al, 2009). However, both we and others have reported that prior to the sudden appearance of the pan-somitic SP1 signals at ~17.5 hpf, there is essentially a background resting level of Ca 2+ within the zebrafish trunk (i.e., from all tissues) for at least 1 hour prior to the onset of SP1 (Figs.…”
Section: Generation Of Muscle-specific Apoaequorin-expressing Transgementioning
confidence: 99%
“…However, both we and others have reported that prior to the sudden appearance of the pan-somitic SP1 signals at ~17.5 hpf, there is essentially a background resting level of Ca 2+ within the zebrafish trunk (i.e., from all tissues) for at least 1 hour prior to the onset of SP1 (Figs. 3Ai, 12Bi and 12Ci; Gilland et al, 1999;Leung et al, 2009).…”
Section: Generation Of Muscle-specific Apoaequorin-expressing Transgementioning
confidence: 99%